Thysanotus tibeticum (Asparagaceae), a new species from Tibet, China - Liu, Guanghua; Lan, Xiaozhong; Zuo, Youwei; Yang, Yubing; Li, Jiaxi; Liao, Xiaomin; Zhang, Jiabin; Deng, Hongping (Phytotaxa, 2024)
Thysanotus tibeticum (Asparagaceae) from Jiali, Tibet, China, is described, illustrated and compared with related species. T. tibeticum appears to be related to T. chinensis and T. patersonii due to the similar growth habit, but it can be easily distinguished by the shape of roots, flowering stems, inflorescence, pedicels, inner petals and anthers. Surprisingly, the new species is the only one of Thysanotus found in the Qinghai-Tibet Plateau. The area is also the highest elevation and northernmost latitude distribution area where Thysanotus have been found.